2001
DOI: 10.1007/bf03019815
|View full text |Cite
|
Sign up to set email alerts
|

Epidural naloxone reduces intestinal hypomotility but not analgesia of epidural morphine

Abstract: Purpose: Epidural morphine is associated with decreased bowel motility and increased transit time. Low doses of intravenous naloxone reduce morphine-induced pruritus without reversing analgesia, but the effect of epidural naloxone on bowel motility has not been studied. Therefore we evaluated bowel motility and analgesia when naloxone was co-administered with morphine into the epidural space.Methods: Forty-three patients having combined thoracic epidural and general anesthesia for subtotal gastrectomy were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 22 publications
0
10
0
1
Order By: Relevance
“…Other data suggest that an ultra‐low dose of naloxone augmented the anti‐nociceptive effect of morphine by enhancing the reuptake of excitatory amino acids from the synaptic cleft . Human studies from 2001 and 2007 imply that applying low doses of naloxone intrathecally could reduce opioid side effects and enhance analgesia . Results in an earlier study suggested that naloxone in low doses could release endorphins, or probably relocate endorphins from receptor sites .…”
Section: Discussionmentioning
confidence: 99%
“…Other data suggest that an ultra‐low dose of naloxone augmented the anti‐nociceptive effect of morphine by enhancing the reuptake of excitatory amino acids from the synaptic cleft . Human studies from 2001 and 2007 imply that applying low doses of naloxone intrathecally could reduce opioid side effects and enhance analgesia . Results in an earlier study suggested that naloxone in low doses could release endorphins, or probably relocate endorphins from receptor sites .…”
Section: Discussionmentioning
confidence: 99%
“…The single study of epidural naloxone reported earlier flatus and first BM vs placebo [33]. It was not possible to compare measures of efficacy for oral alvimopan and epidural naloxone because of the different manner in which outcomes were presented.…”
Section: Postoperative Ileusmentioning
confidence: 99%
“…Cumulative evidence shows that opioids induce inhibitory and/or excitatory modulation of action potentials in sensory neurons [32]. In human studies, a low dose of epidural naloxone enhances analgesia as well as reduces opioid side effects [33][34][35]. Interestingly, a larger dose of naloxone elicited hyperalgesia, whereas a small dose resulted in paradoxical analgesia [36][37][38].…”
Section: Discussionmentioning
confidence: 99%